Effects of polysaccharides from Cordyceps sinensis mycelium on physical fatigue in mice - Yan, Feng; Zhang, Yan; Wang, Beibei (Bangladesh Journal of Pharmacology, 2012)
This study was designed to determine the effects of polysaccharides from Cordyceps sinensis mycelium (CSP) on physical fatigue in mice. The mice were randomly divided into four groups (n = 16 in each group), i.e. control group, low-dose CSP treated group, intermediate-dose CSP treated group and high-dose CSP treated group. The mice in the treated groups received CSP (100, 200 and 400 mg/kg, ig), and the mice in the control group received drinking water ig. After 28 days, a forced swimming test was performed and some biochemical parameters related to fatigue were examined. The present data suggested that CSP could extend the exhaustive swimming time of mice, as well as increase the hepatic glycogen and muscle glycogen levels, and decrease the blood lactic acid and BUN levels. These results indicated that CSP had anti-fatigue effects.